A Case of Status Epilepticus in a Patient Experiencing an Acute Attack of Hereditary Angioedema - Danielle Weinberg; Steven Gayda; Kyle Hultz; Hanan Atia; Brian Kohen; Eric Boccio (Clinical Practice and Cases in Emergency Medicine)
Introduction: Hereditary angioedema (HAE) is a genetic disorder associated with recurrent episodes of angioedema in the absence of urticaria and pruritus. Hereditary angioedema is inherited in an autosomal dominant pattern and results in a quantitative deficiency (HAE type I) or dysfunction (HAE type II) of the C1-esterase inhibitor (C1-INH) protein. A very rare third type of HAE which is associated with normal quantitative and functional levels of C1-INH (HAE-nl-C1-INH) has been described. Case Report: A 54-year-old female with past medical history significant for HAE-nl-C1-INH presented to the emergency department (ED) for an acute attack of HAE and seizures. The patient arrived postictal after experiencing a total of three witnessed seizures, each lasting approximately 30 seconds. After the initial seizure was witnessed in the ED, the patient received 4200 Units of recombinant C1-INH intravenously. The patient’s mental status did not return to baseline, and she experienced two additional seizures. She was given a dose of the kallikrein inhibitor, ecallantide, as well as standard dosing of lorazepam and levetiracetam. The patient returned to her baseline and had no subsequent seizures while in the ED. Inpatient work-up included continuous video electroencephalography monitoring and magnetic resonance imaging of the brain, both of which were normal. The remainder of the inpatient course was uncomplicated, and the patient was discharged home neurologically intact. Conclusion: We present a case of status epilepticus in a patient with HAE-nl-C1-INH. The focus of emergent medical management of status epilepticus includes airway protection, respiratory support, and administration of abortive and prophylactic antiepileptic drugs. The emergency medicine physician should also consider and treat possible underlying etiologies. The treatment of an acute attack of HAE should focus on replacing C1-INH and preventing the formation and limiting the action of bradykinin.